Egypt's Political Prisoners and U.S. Aid - Sprunsansky, Dale (The Washington report on Middle East affairs, 2021)
There are currently an estimated 70,000- 100,000 political prisoners from all walks of life being held in Egyptian prisons. The US' continued support for President Abdel Fattah el-Sisi, despite his willingness to use extreme measures of repression against dissidents, was the subject of a virtual event hosted by several different organizations on Mar 9. Sarah Leah Whitson, executive director of Democracy for the Arab World Now (DAWN), noted that the US sends roughly $1.3 billion in military aid to Egypt annually. She believes this aid should be suspended under the Leahy Law, which prohibits arms transfers to military units violating human rights, and under the Arms Export Control Act, which forbids arms transfers to governments that systematically abuse human rights. Whitson said that for too long, US officials have maintained that their aid can be used as leverage to push for human rights advances in Egypt, or that the aid is necessary for national security and geopolitical interests.